Research of connectivity for wireless sensor networks - HUANG Xiao 1; CHENG Hong-bing 1; YANG Geng1 (Tongxin xuebao)
It was crucial to acquire the knowledge of nodes connectivity before management,application and research of wireless sensor networks when they had been deployed in the interest randomly.Under real environment there can be some nodes called unreachable node in interest,which could not communicate with base station for some reason,for ex-ample there are some nodes lie out of the radio range of base station or the interest range.A scheme to make those un-reachable nodes be able to communicate with base station was proposed.At the same time,a judgment algorithm for nodes connectivity based on a normal wireless sensor networks model was proposed.In simulation two-experiment scheme to test the proposed scheme and judgment algorithm were set.From the results of simulation conclude that the proposed scheme can improve nodes’ connectivity in the interest and the proposed algorithm can judge the connectivity efficiently and accurately.